2019
DOI: 10.1111/his.13897
|View full text |Cite
|
Sign up to set email alerts
|

Multiple KRAS mutations in the non‐mucinous epithelial lining in the majority of mucinous cystic neoplasms of the pancreas

Abstract: Aims Mucinous cystic neoplasms (MCNs) of the pancreas are cystic neoplasms lined by mucinous lining epithelium (MLE) with associated ovarian‐type stroma. Although a non‐MLE (NMLE) can be observed in some MCNs, whether cystic neoplasms with ovarian‐type stroma and NMLE should be classified as MCNs or separately designated is debated. Methods and results To test this, NMLEs were defined as flat or cuboidal epithelial cells without intracytoplasmic mucin. A total of 112 MCNs were reviewed, and the epithelium was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…In present study, 84% (10/12) of cases had a clinical impression of pancreatic cysts, mainly MCNs based on pretreatment imaging studies. As is well-known, ovarian-type stroma is a distinct histologic features of MCNs [28]. As expected, we found ovarian-type stroma in about half (5/12, 42%) of the cases, and all 5 cases with ovarian-type stroma had residual lining mucinous epithelia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In present study, 84% (10/12) of cases had a clinical impression of pancreatic cysts, mainly MCNs based on pretreatment imaging studies. As is well-known, ovarian-type stroma is a distinct histologic features of MCNs [28]. As expected, we found ovarian-type stroma in about half (5/12, 42%) of the cases, and all 5 cases with ovarian-type stroma had residual lining mucinous epithelia.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our results, Oh and colleagues [14] reported that 75% (3/4) of the cases showed marked epithelial ablation (range, 25–100%) in resected pancreatic cysts after ablation. In contrast, in nontreated MCN cases before surgical resection, approximately half of the neoplastic epithelial lining was eroded [28]. Therefore, pancreatic cysts treated with EUS-guided ablation therapy may have a wider area of the cystic wall without covering lining epithelial cells after ablation.…”
Section: Discussionmentioning
confidence: 99%
“…34,38 In Cancer Cytopathology July 2022 pancreatic cystic fluid, the presence of KRAS mutation has been suggested as a highly specific test for mucinous cyst, with a reported sensitivity of 77%. 33,35,36 These results suggest that KRAS mutational analysis has lower sensitivity and specificity in detecting malignancy in biliary tract brushing compared with that in pancreatic solid or cystic lesion FNAs. 24,33,34,38 The differences may be explained by a lower incidence of KRAS mutation rate in cholangiocarcinoma (5%) compared with pancreatic adenocarcinoma (66%), the inclusion of nonmalignant cytology cases in our study cohort, and the nature of overall limited cellularity in bile duct brushing specimens.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, KRAS mutation testing in pancreatic FNA biopsy was reported to have overall sensitivity and specificity of 79% and 100%, respectively 34,38 . In pancreatic cystic fluid, the presence of KRAS mutation has been suggested as a highly specific test for mucinous cyst, with a reported sensitivity of 77% 33,35,36 . These results suggest that KRAS mutational analysis has lower sensitivity and specificity in detecting malignancy in biliary tract brushing compared with that in pancreatic solid or cystic lesion FNAs 24,33,34,38 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation